Infeksi Papaya ringspot virus pada Tanaman Pepaya di Provinsi Nanggroe Aceh Darussalam - Sri Hendrastuti Hidayat; Sari Nurulita; Suryo Wiyono (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Severe mosaic symptoms was observed on papaya plants in Meusa village, Kutablang sub district, Bireun district and Lambaro Teunom village, Lembah Seulawah sub district, Aceh Besar district. Systemic mosaic was found in leaves, stem, twig, and fruit. Reverse transcription-polymerase chain reaction (RT-PCR) was conducted to detect the virus causing mosaic symptoms using universal primer for Potyvirus. Amplification of 320 bp DNA fragment was successfully obtained from leaves and fruits bearing severe mosaic symptoms. Nucleotide sequencing was proceeded using the DNA amplicon as the template. Further sequence analysis indicated that Potyvirus isolates from papaya in Aceh show the highest homology (92.7% to 94.7%) with Papaya ringspot virus (PRSV) from Philippines, Thailand, and Indonesia. This is the first report on PRSV infection on papaya in Nanggroe Aceh Darussalam province. Key words: Potyvirus, RT-PCR, sequencing